One Health of Peripheries: Biopolitics, Social Determination, and Field of Praxis - Baquero, Oswaldo Santos (Frontiers in Public Health, 2021)
Amid the urgency to solve countless and severe health problems, asking what is health or who can and must have it may seem like a waste of time. However, some responses can reveal prevailing practices that divert attention from fundamental problems, thus maintaining privileges and deepening health inequities. One Health of Peripheries arises from these questions and takes three interdependent senses. The first refers to attributes determining the well-being and suffering of peripheral multispecies collectives: a state, a process, the realization of capacities. The second problematizes marginalizing apparatuses that define health and who can and should have it. The third encompasses practices in more-than-human social spaces in which, and through which, One Health is experienced, understood, and transformed. The qualification of health as “one” does not refer to the lack of plurality, nor to the simple aggregation of health fragments (human + animal + environmental), but to the complexity of health in a field with peripheral places, ensuing from margins to privilege those who are inside and legitimize the exploitation of those who are outside. The interaction among margins creates degrees and kinds of privilege and vulnerability that materialize epidemiologic profiles while articulating different peripheral strengths and needs supports a collective resistance to break margins. Social determination, a key concept in the (Latin American) collective health movement, underlies such profiles. However, this movement overlooks the more-than-human dimension of social determination; that is to say, One Health of Peripheries is a blind spot of collective health. The cartography of One Health of Peripheries has unique needs regarding participation, research, and inclusive policies for the decolonial promotion of healthy lifestyles.